Sintesis dan Karakteristik Struktur, Sifat Fisis, dan Sifat Mekanik Komposit Aspal Silika dengan Variasi Komposisi Aspal Silika (20%:80%wt; 15%:85%wt; 10%:90%wt) - Enang Widwiyantoro; Simon Sembiring; Syafriadi Syafriadi; Suprihatin Suprihatin (Journal of Energy, Material, and Instrumentation Technology, 2020)
Synthesis and characterization of asphalt silica composites with various compositions have been carried out 20%: 80%wt; 15%: 85%wt; 10%: 90%wt. Silica synthesis was carried out using the sol-gel method. The materials used are rice husks, solid asphalt, distilled water, gasoline, NaOH 1,5% and HNO3 10%. This research was conducted for knowing the effect variations composition of asphalt silica on the phase structure, physical, and mechanical properties. The results of characterization asphalt silica composites with X-Ray Diffraction (XRD) obtained nothing change of phase and so that the phase structure still amorphous that consist of amorph silica and amorph carbon. The result of water adsorbent testing obtained that all variation was infest the standard, which was above 10%. The result compressive strength testing obtained the variation 15%:85%wt got the highest value amount 47,55 Mpa.